Analisis Faktor Faktor Yang Mempengaruhi Financial Distress Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bei Tahun 2017 – 2020 - Endang Mardiati; Husna, Aulia Rahmawati Rosyadi (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
This study aims to examine and analyze the factors affecting financial distress, including financial ratios consisting of liquidity, leverage, profitability, and activity ratios. The population incorporates companies listed on the Indonesia Stock Exchange, from which 37 samples of mining companies listed on IDX between 2017 and 2020 are selected through purposive sampling method, and analyzed by logistic regression. The results exhibited that profitability and activity ratios present as predictors of financial distress, while this not the case for liquidity and leverage.This study aims to examine and analyze the factors affecting financial distress, including financial ratios consisting of liquidity, leverage, profitability, and activity ratios. The population incorporates companies listed on the Indonesia Stock Exchange, from which 37 samples of mining companies listed on IDX between 2017 and 2020 are selected through purposive sampling method, and analyzed by logistic regression. The results exhibited that profitability and activity ratios present as predictors of financial distress, while this not the case for liquidity and leverage.